Home ground advantage: Local Atlantic salmon have higher reproductive fitness than dispersers in the wild - Mobley KB; Granroth-Wilding H; Ellmen M; Vaha JP; Aykanat T; Johnston SE; Orell P; Erkinaro J; Primmer CR (AMER ASSOC ADVANCEMENT SCIENCE, 2025)
A long-held, but poorly tested, assumption in natural populations is that individuals that disperse into new areas for reproduction are at a disadvantage compared to individuals that reproduce in their natal habitat, underpinning the eco-evolutionary processes of local adaptation and ecological speciation. Here, we capitalize on fine-scale population structure and natural dispersal events to compare the reproductive success of local and dispersing individuals captured on the same spawning ground in four consecutive parent-offspring cohorts of wild Atlantic salmon (Salmo salar). Parentage analysis conducted on adults and juvenile fish showed that local females and males had 9.6 and 2.9 times higher reproductive success than dispersers, respectively. Our results reveal how higher reproductive success in local spawners compared to dispersers may act in natural populations to drive population divergence and promote local adaptation over microgeographic spatial scales without clear morphological differences between populations.